Learn Java 17 programming - Samoylov, Nick (Packt Publishing Ltd., 2022)
Java is one of the most preferred languages among developers. It is used in everything right from smartphones and game consoles to even supercomputers, and its new features simply add to the richness of the language. This book on Java programming begins by helping you learn how to install the Java Development Kit. You'll then focus on understanding object-oriented programming (OOP), with exclusive insights into concepts such as abstraction, encapsulation, inheritance, and polymorphism, which will help you when programming for real-world apps. Next, you'll cover fundamental programming structures of Java such as data structures and algorithms that will serve as the building blocks for your apps with the help of sample programs and practice examples. You'll also delve into core programming topics that will assist you with error handling, debugging, and testing your apps. As you progress, you'll move on to advanced topics such as Java libraries, database management, and network programming and also build a sample project to help you understand the applications of these concepts. By the end of this Java book, you'll not only have become well-versed with Java 17 but also gained a perspective into the future of this language and have the skills to code efficiently with best practices.